Building Well-Being Amid Economic Transition: The Role of Work Environment in Shaping Employee Well-Being - Maharani, Dheyah; Pertiwi, Talitha Lintang (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2026)
A supportive work environment is considered an important factor in enhancing employee well-being; however, empirical studies within economically transitional regions remain limited. This study aims to examine the effect of the work environment on employee well-being among workers in the Bangka Belitung Islands, a region undergoing economic transition from the mining sector to formal employment sectors. A quantitative approach with a cross-sectional design was employed involving 154 respondents selected using simple random sampling. Data were collected through an online questionnaire consisting of the Supportive Work Environment Scale and Employee Well-Being Scale. Data were analyzed using simple linear regression to examine the primary effect of Supportive Work Environment on Employee Well-Being, followed by multiple linear regression analysis to identify the contribution of each dimensional construct using SPSS version 27. The results indicated a significance value of < 0.001 with an F value of 153.135. The coefficient of determination (R² = 0.502) showed that the work environment contributed 50.2% to the variance in employee well-being. Partially, Perceived Climate and Perceived Organizational Support emerged as dominant dimensions, while Peer Group Interaction and Supervisory Support showed no significant effects. These findings highlight the importance of a collaborative work climate in improving employee well-being in economically transitional regions.Lingkungan kerja yang suportif dipandang sebagai faktor penting dalam meningkatkan employee well-being, namun kajian empiris pada konteks daerah transisi ekonomi masih terbatas. Penelitian ini bertujuan untuk menguji pengaruh lingkungan kerja terhadap employee well-being pada pekerja di Kepulauan Bangka Belitung yang tengah mengalami transisi ekonomi dari sektor pertambangan ke sektor formal. Penelitian menggunakan pendekatan kuantitatif dengan desain cross-sectional melibatkan 154 responden yang dipilih melalui teknik simple random sampling. Data dikumpulkan menggunakan kuesioner daring yang terdiri dari Supportive Work Environment Scale dan Employee Well-Being Scale. Analisis data dilakukan menggunakan regresi linear sederhana untuk menguji pengaruh utama Supportive Work Environment terhadap Employee Well-Being, yang dilanjutkan dengan regresi linear berganda untuk mengidentifikasi kontribusi masing-masing dimensi variabel menggunakan SPSS versi 27. Hasil menunjukkan signifikansi < 0,001 dengan nilai F sebesar 153,135. Nilai koefisien determinasi (R²) sebesar 0,502 menunjukkan kontribusi lingkungan kerja sebesar 50,2% terhadap variasi employee well-being. Secara parsial, Perceived Climate dan Perceived Organizational Support menjadi dimensi paling dominan, sementara Peer Group Interaction dan Supervisory Support tidak berpengaruh signifikan. Temuan ini menegaskan pentingnya iklim kerja kolaboratif dalam meningkatkan kesejahteraan pekerja pada wilayah ekonomi transisional.